2012
DOI: 10.1108/00400911211274882
|View full text |Cite
|
Sign up to set email alerts
|

Assessment: examining practice in entrepreneurship education

Abstract: PurposeThe purpose of this paper is to develop knowledge about the nature of student assessment practice in entrepreneurship education.Design/methodology/approachThis paper introduces general assessment practice issues and highlights key considerations. It explains prior research on assessment practice in entrepreneurship education and argues that there is too little empirical research on the subject. Finally, it outlines a typology of entrepreneurship education that highlights variation between different: for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
286
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(294 citation statements)
references
References 27 publications
0
286
0
8
Order By: Relevance
“…Those that focused on developing skills 'for entrepreneurship' predominantly used 'business planning' formats and assumed innovative capacity, whilst those categorized as learning 'through' the practice of entrepreneurship were less frequently encountered in the data. In other words, most of the assessment collated in the study by Pittaway and Edwards (2012) was based on knowledge retention, as opposed to the ability to act creatively through 'knowledge harvesting' in response to shifting demands and ambiguous situations, as is the case we shall describe in design-based studies.…”
Section: Assessing Creativity Through Learning Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Those that focused on developing skills 'for entrepreneurship' predominantly used 'business planning' formats and assumed innovative capacity, whilst those categorized as learning 'through' the practice of entrepreneurship were less frequently encountered in the data. In other words, most of the assessment collated in the study by Pittaway and Edwards (2012) was based on knowledge retention, as opposed to the ability to act creatively through 'knowledge harvesting' in response to shifting demands and ambiguous situations, as is the case we shall describe in design-based studies.…”
Section: Assessing Creativity Through Learning Outcomesmentioning
confidence: 99%
“…Moreover, Pittaway and Edwards (2012), in their international review of entrepreneurship education, focused on collated evidence of current assessment practice. Their findings revealed that -despite the desire to develop innovative approaches for entrepreneurship education -most educational practice was still fairly traditional and reliant on the notion of being consistently correct.…”
Section: Assessing Creativity Through Learning Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is very little research dealing with assessment in entrepreneurial education (Pittaway and Edwards, 2012), it is increasingly clear that learner-led approaches are required. For Sagar (2015), students should co-design, co-teach and co-assess entrepreneurial education activities through formative and peer assessment.…”
Section: Italian Vocational Teachersmentioning
confidence: 99%
“…Since a university's mission is somehow linked to entrepreneurship, the academic programs have three different ways of approaching the issue, namely: "about", "for" and "through" entrepreneurship Pittaway & Edwards, 2012). The first ones are more traditional and adopt a theoretical perspective; they focus on delivering knowledge about what entrepreneurship is and how an entrepreneur should behave (Pittaway & Edwards, 2012).…”
Section: Abstract (In Polish)mentioning
confidence: 99%